Kinematic Geometry of Circular Surfaces With a Fixed Radius Based on Euclidean Invariants - Cui, Lei; Wang, D.; Dai, J. (ASME Press, 2009)
A circular surface with a fixed radius can be swept out by moving a circle with its center following a curve, which acts as the spine curve. Based on a system of Euclidean invariants, the paper identifies those circular surfaces taking lines of curvature as generating circles and further explores the properties of the principal curvatures and Gaussian curvature of the tangent circular surfaces. The paper then applies the study to mechanism analysis by proving the necessary and sufficient condition for a circular surface to be generated by a serially connected C'R, HR, or RR mechanism, where C' joint can be visualized as a special H joint with a variable pitch of one degree of freedom. Following the analysis, this paper reveals for the first time the relationship between the invariants of a circular surface and the commonly used D-H parameters of C'R, HR, and RR mechanisms.